GR_GERICHTE SK1 2021 38 vom 9. Dezember 2022 , 2C_350/2023 vom 25.02.2025 - GR Gerichte (2022)
mehrfache sexuelle Handlungen mit einem Kind gemäss Art. 187 Ziff. 1 StGB etc. | StGB 187-200 Sexuelle Integrität